Customer retention in MPH Bookstore Great Eastern Mall outlet / Wan Shazana Abd Aziz - Abd Aziz, Wan Shazana (2010)
In maintaining the customer retention, the case studies have taken place in MPH Bookstore Great Eastern Mall. The issue that has been arising in this company is the dissatisfaction of the customer towards the company and how the company take an action to retain the valuable customer as their loyal customer. The method that has been used based on selected monthly sale, customer retention rate calculation, observation and interview with the selected staff. Based on the data, the company have low retention rate based on the selected month. Furthermore, the data that have been collected shows there are different group of the customer needs and wants towards the company. From this, the recommendation has been inserted in serving the customer based on their group and needs suitable in achieving the goals and increasing the customer retention rate.